THE CATEGORY OF INSENSITIVITY IN PHRASEOLOGICAL UNITS AND THEIR SPECIFIC FEATURES IN ENGLISH, RUSSIAN AND UZBEK LANGUAGES - HOMIDOVA NARGIZAXON NURAHMAD QIZI (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The words that a person uses in everyday life induce in his mind an idea of ​​the world around him, of society, of man himself. The transfer of information about this objective reality is also expressed in more complex linguistic units, phraseological units. The use of phraseology gives speech liveliness and colorfulness. Frequently to achieve a certain speech effect of simple words is not enough. Love, mockery, irony, bitterness and your attitude to what is happening- all this can be expressed more emotionally and exactly.